Pemetaan Penelitian seputar Bank CIMB Niaga Syariah dan Konvensional: Studi Bibliometrik VOSviewer dan Literature Review - Wasilatur Rohimah; Eka Wahyu Hestya Budianto; Nindi Dwi Tetria Dewi (Jurnal Ekonomi Manajemen Perbankan, 2023)
This study aims to determine the development of research around CIMB Niaga Islamic and Conventional Bank. The research was conducted from 2011 to 2022, by searching national journals indexed by Sinta via the Garuda website, with the keyword â€œCIMB Niagaâ€. Based on the search results, there were 99 research articles, then inputted into the VOSviewer application and analyzed descriptively through a literature review study. The results showed that the number of publications had increased significantly every year. Furthermore, based on the results detected using the VOSviewer application, research related to CIMB Niaga Bank is divided into 8 clusters and 116 items. Meanwhile, based on the results of a literature review study, there are 8 main themes related to CIMB Niaga Islamic and Conventional Bank.